Kebermaknaan Hidup Susteran Usia Dewasa Madya - Ilmi, Fadhilah Nur; Nilawaty, Azzah (Flourishing Journal, 2025)
The meaning of life is a crucial value, as discovering it can lead to true happiness. This qualitative case study explores the process of finding life’s meaning through the life journey of Sister L. The study applies pattern matching and explanation-building analysis to examine how experiences, attitudes, and creativity influence her understanding of life’s purpose. Data were collected through interviews, observations, and documentation. Sister L’s journey reveals that personal experiences, reflective attitudes, and creative expression contribute significantly to the development of self-understanding and a mature self-concept. Spiritual maturity and continuous learning from life experiences guided her in setting meaningful life goals and sustaining strong personal commitments. Support from her social environment also played a vital role in reinforcing her path as a religious sister. Her deep experiences of suffering and reflection eventually led her to find life’s meaning when she joined the Compagnia Missionaria del Sacro Cuore congregation. Through disciplined routines and consistency, Sister L gradually achieved her life goals, found inner satisfaction, and reached self-actualization. Her final life purpose is now centered on readiness to face God. This study offers valuable insight into life’s meaning and decision-making, particularly for individuals choosing a solitary or celibate life path. AbstrakMakna hidup menjadi nilai yang penting karena jika seseorang mampu menemukan arti hidupnya maka kebahagiaan akan muncul. Peneliti menggunakan jenis penelitian kualitatif pendekatan studi kasus. Menggunakan metode analisis kombinasi pattern matching dengan analisis explanation building, fokus menganalisis aspek kebermaknaan hidup pada tahapan alur hidup suster dan menggali pengaruh proses penemuan makna hidup. Pengumpulan data dengan wawancara, observasi, dan dokumentasi. Aspek-aspek pengalaman, sikap, dan kreativitas dapat mempengaruhi proses pencarian makna hidup dari Suster L. Suster L menemukan makna hidup melalui pengalaman, sikap, dan kreativitas yang membentuk pemahaman diri dan kematangan konsep diri. Pembelajaran dari pengalaman hidup serta kematangan rohani membantunya menentukan tujuan dan komitmen hidup. Dukungan sosial turut memperkuat tekadnya sebagai suster. Pengalaman penderitaan dan pemaknaan hidup membawanya pada arti hidup saat bergabung dengan kongregasi Compagnia Missionaria del Sacro Cuore. Dengan menjalani rutinitas secara konsisten, ia berhasil mencapai tujuan-tujuan hidup, merasakan kepuasan, dan mengaktualisasikan diri. Kini, tujuan akhirnya adalah kesiapan untuk menghadap Tuhan. Dari penelitian ini diharapkan dapat memberikan wawasan baru untuk masyarakat luas mengenai pandangan hidup dan pemilihan keputusan, terutama pada individu yang memutuskan untuk hidup melajang dan sendiri.